Mixing enhancement in supersonic jet flow via air tabs - Ong, Lawrance Yin Keat. (2009)
Research in supersonic jet mixing enhancement has seen a revival with the increased awareness of environmental impacts aircrafts have as well as with the advent of the scramjet. Passive and active means or mixing enhancement haven been researched into, and while delta/solid tabs have proved to be the best in terms of entrainment, air tabs have shown to be able to reproduce the results obtained by the delta/solid tab in subsonic regimes. In this paper, air tabs would be compared to a delta/solid tab in a supersonic regime. The primary jet would be at M=1.3 while the secondary jet would be at M=1.0.